Terminal alkyl chain tuning of small molecule donor enables optimized morphology and efficient all-small-molecule organic solar cells. (April 2022) - Yang, Liyan; Qin, Jinzhao; Li, Sunsun; Zhang, Jianqi; Yang, Yang; Cao, Bingqiang; He, Chang; Hou, Jianhui
Abstract: Modulation of the interfacial molecular orientation and molecular packing behaviour is essential for fine-tuning the nanoscale morphology toward efficient non-fullerene all-small-molecule organic solar cells (NFSM-OSCs) due to the anisotropic molecular structure of electron donors (D) and acceptors (A). Currently, the design of active-layer material to obtain favourable nanoscale morphology is still quite challenging. This work developed four new small molecular donors, TBCA-CX (X = 2, 4, 6, and 8), with the same conjugated skeleton but different terminal alkyl chains. The GIWAXS measurement results reveal that the predominant molecular orientation of pristine TBCA-CX films began to change from edge-on to face-on with the increased terminal alkyl chains length. Furthermore, the non-fullerene acceptor IT-4F was used to fabricate NFSM-OSCs with the new donor compounds. Finally, the TBCA-C4: IT-4F blend formed a more favourable face-to-face orientation at the D/A interface and a more compact molecular stacking as proved from GIWAXS characterization, which is beneficial for charge transfer and charge carrier transport. As a result, the TBCA-C4-based device exhibited a higher power conversion efficiency (PCE) of 9.21%, while its analogs showed PCEs less than 8%. These results provide an insight to understand the impact of molecular design of interfacial molecular orientation and molecular packing behaviour on photovoltaic performance in NFSM-OSCs. Graphical abstract: Image 1